Collins English for life: Reading Anna Osborn B1+ Intermediate - Osborn, Anna (Tp. Hồ Chí Minh: Tổng hợp Tp. Hồ Chí Minh ; Công ty Nhân Trí Việt, 2021)
Collins Reading presents 20 different texts with exercises to help you develop the skills to read anything you come across.